2022-RA-602-ESGO Prognostic factors for recurrence in adult-type granulosa cell tumours of the ovary and survival outcomes after secondary and tertiary cytoreductive surgery: a UK population-based cohort study. (20th October 2022) - Tranoulis, Anastasios; Audrey Kwong, Fong Lien; Elattar, Ahmed; Singh, Kavita; Balega, Janos
Abstract : Introduction/Background: To ascertain the clinicopathological and treatment factors of recurrent ovarian adult-type granulosa cell tumours (AGCTO) and evaluate outcomes of women who underwent secondary and tertiary cytoreductive surgery (CRS) for recurrent AGCTO. Methodology: This was a retrospective cohort study, spanning the period 2000–2022. Population-based prospectively collected data on AGCTO were retrieved via the Pan-Birmingham Gynaecological Oncology database. 38 women with AGCTO were enrolled. Clinicopathological, and treatment data were analysed to identify plausible predictors of recurrence. Survival analysis was performed via the Kaplan-Meier method, log-rank test and Cox-regression. Census day was April 1st, 2022. Statistical significance was set at p-value<0.05. Results: The median age at diagnosis was 48.5 years. 78.96% of women had stage IA, 10.52% stage IC, and 10.52% stage IIIC, respectively. All women underwent primary surgical staging, including eight (21.1%) women who underwent fertility-sparing surgery (FSS). During follow-up (median, 128.5 months), 11 recurrences (28.9%) were observed. The mean time to recurrence was 235.11 months. The cumulative recurrence free rate for the first 3 and 5 years was 97.4% and 89.5%, respectively. There was a significant correlation between tumour size ( p-value =0.006), stage ( p-value =0.0008), solid component ( p-value =0.02), moderate/severe nuclei atypia ( p-value =0.0004), necrosis ( p-value =0.04), mitotic index (MI) ( p-value =0.0001), hormonal treatment ( p-value =0.02), and recurrence. In multivariate analysis, MI (HR=11.95, p-value =0.03) was found to be independent prognosticator. FSS was not associated with recurrence. Six women underwent complete secondary cytoreductive surgery (CRS). The median time interval between the first and second recurrence (R-PFS) was 59 months. Two women underwent complete tertiary CRS for three and four subsequent recurrences, respectively. Conclusion: Surgical management represents the cornerstone of treatment in AGCTO. Several pathological factors should be taken in consideration when tailoring post-operative management. The role of post-operative chemotherapy and hormonal therapy remains vague. Secondary and tertiary CRS should be offered at highly experienced centres to improving R-PFS.